Resilience of benthic ecosystem C-cycling to future changes in dissolved oxygen availability. (March 2019) - White, Carol M.; Woulds, Clare; Cowie, Greg L.; Stott, Andrew; Kitazato, Hiroshi
Abstract: In marine sediments, the availability, cycling and burial of organic carbon (OC), the size and composition of the faunal community, and the availability of dissolved oxygen (DO) are closely coupled. In light of expected expansions in marine hypoxia and of oxygen minimum zones (OMZs) in particular, it is now necessary to de-convolve DO from the frequently co-varying factors OC concentration and faunal biomass, in order to understand the effect of changing dissolved oxygen (DO) concentrations on the magnitude and pattern of biological processing of organic carbon (OC). This is especially important on the continental slope, a significant location for C cycling and burial. In this study, stable isotope tracer experiments were conducted at three sites with contrasting ambient DO concentrations of 0.5, 2.8 and 21.2 μM (at depths of 530m, 812m and 1140m respectively) on the Indian continental margin. Experiments were conducted both at ambient DO concentrations, and also, for the first time, under manipulated DO concentrations both 5% above and below ambient. The 13 C label was added as algal detritus, and traced through the processes of respiration, and uptake into bacterial biomass, and into metazoans and foraminifera. Total C biological processing under ambient DO conditions was similar across all three sites, suggesting that benthic communities are well adapted to local conditions, such that OC processing is optimised even at severely hypoxic sites. DO manipulation produced changes in the pattern of OC processing by the benthic community. Oxygen manipulations in both directions resulted in decreases in total community respiration, except at the most hypoxic site. Bacterial uptake, in contrast, increased in response to all DO manipulations. Faunal 13 C uptake tended to increase with increased DO. At the most hypoxic site (0.5 μM) this was attributable to increased foraminiferal activity, whereas at the most oxygenated site (21.2 μM) it was the metazoans that showed increased biomass-specific 13 C uptake. Similarly, decreases in DO tended to reduce faunal 13 C uptake, with metazoans disproportionately affected where they were already living at the lower end of their DO tolerance (i.e. 2.8 μM). Thus, the taxa most affected by DO manipulation depended on antecedent DO conditions. The total capacity of the benthic community to process freshly deposited OC (i.e. respiration plus uptake by bacterial and different fauna) increased following upwards manipulation of DO at the 0.5 μM site, but was not adversely affected by downwards manipulation of DO. Thus, results suggest that benthic communities possess some functional resilience, and that future expansion of marine hypoxia, while impacting benthic ecosystem structure, may not have as marked an effect on biological C processing.